2014
DOI: 10.1097/tp.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Nonmelanoma Skin Cancer Incidence Rates in Kidney Transplant Recipients in Ireland

Abstract: Appropriate modeling of incidence trends in NMSC among RTRs is a valuable surveillance exercise for assessing the impact of change in clinical practices over time on the incidence rates of skin cancer in RTRs. It can form the basis of further research into unexplained regional variations in NMSC incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…There is a well‐established association between aging and cancer incidence and the association between time since transplantation, which equates to duration of immunosuppression, and risk of malignancy was evident in this cohort and has been previously recognized . A recent investigation of the long‐term risk of NMSC in an Irish kidney transplant population suggested that there was an early increase in excess risk of cancer following transplantation but that the magnitude of this excess fold risk subsequently remained constant . It is likely that the interaction between this stable transplant‐related excess risk and the exponential increase in cancer incidence, which occurs with aging, explains the relentless rise in cancer incidence in transplant patients over time.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…There is a well‐established association between aging and cancer incidence and the association between time since transplantation, which equates to duration of immunosuppression, and risk of malignancy was evident in this cohort and has been previously recognized . A recent investigation of the long‐term risk of NMSC in an Irish kidney transplant population suggested that there was an early increase in excess risk of cancer following transplantation but that the magnitude of this excess fold risk subsequently remained constant . It is likely that the interaction between this stable transplant‐related excess risk and the exponential increase in cancer incidence, which occurs with aging, explains the relentless rise in cancer incidence in transplant patients over time.…”
Section: Discussionsupporting
confidence: 52%
“…In the study of NMSC incidence in kidney transplant recipients in Ireland, two comparable populations were managed in separate jurisdictions with different approaches to immunosuppression. There was inferior early graft survival but a significant reduction in the development of NMSC in the region with a conservative approach to immunosuppression . This suggests that the long‐term risk of cancer in recipients with an extended period of graft function may be modified by minimization of the immunosuppressive burden.…”
Section: Discussionmentioning
confidence: 99%
“…Although era of transplantation was not a significant predictor of skin cancer, we felt it was appropriate to include it as a covariate as to account for differences in immunosuppression regimens which are known to influence the onset of NMSC posttransplant. 41 To investigate the impact of PRS on time to NMSC, we carried out a Cox proportional hazards analysis adjusting for age, era, eight PCs, and clinical center for transplantation (site) where appropriate (see Section 2,4). The Cox analysis was carried out separately for each site and then meta-analyzed across sites.…”
Section: Re Sultsmentioning
confidence: 99%
“…This is clinically significant for solid organ transplant recipients, in particular renal transplant recipients, many of whom receive long‐term immunosuppressive therapy. The incidence of cutaneous SCC in transplant patients shows marked geographic variation and has exhibited a general decline in recent years . Nonetheless, cutaneous SCC is the most common malignancy in renal transplant patients and they may still have as much as an 82‐fold increased risk for invasive cutaneous SCC compared to the general population .…”
Section: High‐risk Factors In Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%